WRITTEN ASSIGNMENTS ON PARADIGMS, DISCIPLINARITY, AND RESEARCH INTEGRATION - DOE, TANIS (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
1. Write a short piece (around 3-5 pages) which documents your understanding of at least two paradigms in disability studies. 2. In this assignment you must demonstrate familiarity with issues and readings from the course. Selecting one or more disciplines/professions (public health, social work, sociology, law) identify the ideological or philosophical underpinnings of the related policies or services. 3. In this assignment you must demonstrated the ability to collect and analyse research findings, add your own perspective, support it with evidence and make recommendations for change.